Casey Jones - Gleiter, Jan, 1947-; Thompson, Kathleen; Balistreri, Francis (Milwaukee : Raintree Childrens Books, 1987)
The life of the railroad engineer, famous for always bringing his train in on time, and whose last ride on the Cannonball Express inspired the well-known ballad.
Keywords: Jones, Casey, -- 1863-1900 -- Juvenile literature; Jones, Casey, -- 1863-1900; Locomotive engineers -- United States -- Biography -- Juvenile literature; Locomotive engineers